THE EFFECT OF STRATEGIC PHYSIOGNOMY ENHANCING ORGANIZATIONAL SUCCESS OF TOURISTIC ORGANIZATIONS: AN EXPLORATORY STUDY IN THE MINISTRY OF CULTURE, TOURISM ANTIQUITIES - Safaa Atallah Soluman; Dina Hamid Jamal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The current study aims to test relationship of effect variables study Physiognomy Strategy (PS) as an independent variable by dimensions in organizational success(OS) our milestone variable For a sample of leaders in Ministry of Culture, Tourism Antiquities by analyzing a sample of leaders, Tourism and Antiquities, with a total of (182) questionnaires distributed among (general managers, associate The general manager, department heads, people officials) as well as personal interviews with The directors in ministry included relationship between strategic leadership and success Organizational(OS) These variables have recently received increased attention as they are topics mission and the fundamental in the future of organizations, the variable included three dimensional (empowerment .Inspiration, Deep understanding (DU), But , Other variable included five sub-dimensions (resources, structure Organizational, practical management, knowledge management(Km)), those interacted to form framework of world The study revolves around it, main , sub-impositions emerged in order achieve goal of study Mentioned above.